2013
DOI: 10.1021/ja311700u
|View full text |Cite
|
Sign up to set email alerts
|

Fused Dithienogermolodithiophene Low Band Gap Polymers for High-Performance Organic Solar Cells without Processing Additives

Abstract: ABSTRACT:We report the synthesis of a novel ladder-type fused ring donor, dithienogermolodithiophene, in which two thieno [3,2-b]thiophene units are held co-planar by a bridging dialkyl germanium. Polymerisation of this extended monomer with N-octylthienopyrrolodione by Stille polycondensation afforded a polymer, pDTTG-TPD, with an optical band gap of 1.75 eV combined with a high ionization potential. Bulk heterojunction solar cells based upon pDTTG-TPD:PC71BM blends afforded efficiencies up to 7.2% without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 41 publications
1
118
1
1
Order By: Relevance
“…The results of many of these studies have been published previously. 7,37,40,56,[78][79][80][81][82][83][84][85][86][87][88] This large body of data has allowed us to identify statistically significant empirical materials correlations which can be difficult to observe from smaller data sets. In this perspective we aim to summarise some of the key findings of these studies.…”
Section: Transient Absorption Assay Of Charge Photogeneration Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of many of these studies have been published previously. 7,37,40,56,[78][79][80][81][82][83][84][85][86][87][88] This large body of data has allowed us to identify statistically significant empirical materials correlations which can be difficult to observe from smaller data sets. In this perspective we aim to summarise some of the key findings of these studies.…”
Section: Transient Absorption Assay Of Charge Photogeneration Efficiencymentioning
confidence: 99%
“…These advances in efficiency have largely been achieved by the synthesis and testing of new materials and device architectures, including in particular new photoactive layer materials whose energy levels have been modulated to achieve higher output voltages and / or improved photocurrent generation due to lower optical bandgaps. 1,2,4,7,9 However, at present our ability to predict device function from materials structure remains relatively limited. As a consequence, the vast majority of new materials tested have not performed better than the on-going state of the art, typically achieving significantly lower device performance than that predicted by simple, energy level based, device models.…”
Section: Introductionmentioning
confidence: 99%
“…(3,3′-Dibromo-2,2′-bithieno [3,2-b]thiene-5,5′-diyl)bis(trimethylsilane) (1) was synthesized following a similar method in previous reports. 24 4,9-Dibromonaphtho[1,2-c:5,6-c]bis [1,2,5]thiadiazole was purchased from Lumtec. Flash chromatography (FC) was carried out on silica gel (Merck Kieselgel 60 grade 40−63 μm F254) using flash techniques.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Followed by PDTS-TPD and PDTG-TPD, dithienogermolodithiophene (DTTG) was also incorporated as building blocks in TPD-based polymers because of the potentials of extended conjugation length and improved coplanarity. Very recently, Heeney et al [154] reported the first synthesis of a novel ladder-type fused ring donor, DTG, in which two thieno [3,2-b]thiophene units are held coplanar by a bridging dialkyl germanium (Ge). Polymerization of DTTG with TPD afforded a polymer, PDTTG-TPD, with an optical band gap of 1.75 eV combined with a HOMO level of −5.68 eV.…”
Section: Thienopyrroledione (Tpd)-based Polymersmentioning
confidence: 99%